Pemanfaatan Limbah Jerami Padi Di Desa Garon Kecamatan Balerejo, Kabupaten Madiun - Rhofita, Erry Ika; Chana AW, Liliek (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2019)
Greenhouse gas emissions are an environmental issue that has an impact on climate change and global warming. One of the cause is the burning of rice straw after harvest in the field. The existence of majelis taklim is not only religious facilities, and it’s as a way to community empowerment. QS. As-Sad 27 and QS Al-Anbiya 16 explains that everything created by Allah SWT with all aims and benefits. Generally, rice straw is perception as a waste, but if it utilised with science and technology will be able to improve the use of value and economic value. 82,19% and 79,45% of the members of majlis taklim have perception that utilizing of rice straw can improve their income and part of the sustainable environmental management. And 94,25% of the members of majelis taklim did not utilise rice straw and burned it in the field. They did not have skills and knowledge to utilise of the rice straw. Furthermore, training and education must be conducted regularly.